2010
DOI: 10.1021/ie901469c
|View full text |Cite
|
Sign up to set email alerts
|

Effective Cr(VI) Removal from Simulated Groundwater through the Hydrotalcite-Derived Adsorbent

Abstract: We investigated the feasibility of using calcined hydrotalcite (CHT) as the adsorbent of chromate to treat Cr(VI)-contaminated water through column tests under varied conditions. The column tests reveal that CHT can take up 34.3−44.7 mg(Cr)/g when the Cr(VI) concentration in the influent varies over a range of 50−200 mg/L (e.g., 0.96−3.85 mM) with pH 6−7 at 298 K. This uptake capacity is only reduced to 29.1 mg(Cr)/g when HCO3 − (1.0 mM) and Cl− (1.0 mM) coexist in the influent. We note that the treated water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Several treatment methods for Cr(VI) removal from industry wastewater have been established, i.e., electrochemical precipitation, ion exchange, membrane ultrafiltration, reverse osmosis, reduction, and adsorption [1][2][3][4][5]. However, most of these methods are costly due to operational, treatment and sludge disposal costs.…”
Section: Introductionmentioning
confidence: 99%
“…Several treatment methods for Cr(VI) removal from industry wastewater have been established, i.e., electrochemical precipitation, ion exchange, membrane ultrafiltration, reverse osmosis, reduction, and adsorption [1][2][3][4][5]. However, most of these methods are costly due to operational, treatment and sludge disposal costs.…”
Section: Introductionmentioning
confidence: 99%
“…2) corresponded to the characteristic vibration of Cr (VI). 30 The FTIR spectra did not show such a strong absorbance intensity of Cr (VI), when P and Cr (VI) were simultaneously absorbed by CLDH, which demonstrated that the presence of P decreased the adsorption of Cr (VI) and competitive adsorption between P and Cr (VI) occurred.…”
Section: Resultsmentioning
confidence: 92%
“…29 Furthermore, the broad peaks were attributed to the formation of Mg-Al mixed oxides. In the current column test, it is assumed that CLDH can adsorb ions via three mechanisms: (i) electrostatic attraction on surface, (ii) ion exchange interaction between anions and hydroxyl ions, (iii) regeneration of its initial layered structure, as expressed by the following reaction: 29,30 (1)…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, a family of anionic clay materials, hydrotalcite-like materials (HTs) have shown a high adsorption capability for various anions [10][11][12][13], such as chromate (Cr(VI)), exhibiting the potentiality as PRB reactive media to remove this soil contaminant. HTs are exemplified by the naturally existing hydrotalcite (Mg 6 Al 2 (OH) 16 [14]. Its most important property is the high anion exchange capacity.…”
Section: Introductionmentioning
confidence: 99%